+0

# :)))))

+1
47
2
+110

:)

http://prntscr.com/j35u6u

Someone else asked this question, but I'm also confused, could someone explain how this integral was obtained. I don't understand where the 1- part comes from

quilly  Apr 10, 2018
Sort:

#1
+19207
+2

http://prntscr.com/j35u6u

Someone else asked this question, but I'm also confused, could someone explain how this integral was obtained.
I don't understand where the 1- part comes from

$$\mathbf{\displaystyle 4\int \limits_{0}^{D} d\sigma\ \sigma^2\ e^{-2\sigma} = \ ?}$$

1. Apply Integration By Parts:
Formula:

$$\text{Let u = \sigma^2 } \qquad u' = 2\sigma \\ \text{Let v' = e^{-2\sigma} } \qquad v = \int d\sigma \ e^{-2\sigma} = -\frac{1}{2}e^{-2\sigma}$$

$$\begin{array}{|rcll|} \hline \int \limits_{0}^{D} d\sigma\ \underbrace{\sigma^2}_{=u}\ \underbrace{e^{-2\sigma}}_{=v'} &=& \left[ \underbrace{\sigma^2}_{=u} \underbrace{\left( -\frac{1}{2}e^{-2\sigma}\right)}_{=v} \right]_{0}^{D} -\int \limits_{0}^{D} d\sigma\ \underbrace{2\sigma}_{=u'} \underbrace{\left( -\frac{1}{2}e^{-2\sigma}\right)}_{=v} \\\\ &=& \left[ -\frac{1}{2}e^{-2\sigma}\sigma^2\right]_{0}^{D} +\int \limits_{0}^{D} d\sigma\ e^{-2\sigma}\sigma \\\\ &=& -\frac{1}{2}e^{-2D}D^2 +\int \limits_{0}^{D} d\sigma\ e^{-2\sigma}\sigma \\ \hline \end{array}$$

2. Apply Integration By Parts:

$$\text{Let u = \sigma } \qquad u' = 1 \\ \text{Let v' = e^{-2\sigma} } \qquad v = \int d\sigma \ e^{-2\sigma} = -\frac{1}{2}e^{-2\sigma}$$

$$\begin{array}{|rcll|} \hline \int \limits_{0}^{D} d\sigma\ \underbrace{e^{-2\sigma}}_{=v'} \underbrace{\sigma}_{=u} &=& \left[ \underbrace{\sigma}_{=u} \underbrace{\left( -\frac{1}{2}e^{-2\sigma}\right)}_{=v} \right]_{0}^{D} -\int \limits_{0}^{D} d\sigma\ \underbrace{1}_{=u'} \underbrace{\left( -\frac{1}{2}e^{-2\sigma}\right)}_{=v} \\\\ &=& D \left( -\frac{1}{2}e^{-2D}\right) +\int \limits_{0}^{D} d\sigma\ \frac{1}{2}e^{-2\sigma} \\\\ &=& -\frac{1}{2} e^{-2D}D + \frac{1}{2} \int \limits_{0}^{D} d\sigma\ e^{-2\sigma} \\\\ &=& -\frac{1}{2} e^{-2D}D + \frac{1}{2} \left[ -\frac{1}{2}e^{-2\sigma} \right]_{0}^{D} \\\\ &=& -\frac{1}{2} e^{-2D}D + \frac{1}{2} \left[ -\frac{1}{2}e^{-2D} - (-\frac{1}{2}e^{-2\cdot 0})\right] \\\\ &=& -\frac{1}{2} e^{-2D}D + \frac{1}{2} \left[ -\frac{1}{2}e^{-2D} - (-\frac{1}{2}e^{0})\right] \\\\ &=& -\frac{1}{2} e^{-2D}D + \frac{1}{2} \left[ -\frac{1}{2}e^{-2D} - (-\frac{1}{2}\cdot 1)\right] \\\\ &=& -\frac{1}{2} e^{-2D}D + \frac{1}{2} \left[ -\frac{1}{2}e^{-2D}+\frac{1}{2} \right] \\\\ &=& -\frac{1}{2} e^{-2D}D - \frac{1}{4} e^{-2D} + \frac{1}{4} \\ \hline \end{array}$$

$$\begin{array}{|rcll|} \hline \mathbf{4\int \limits_{0}^{D} d\sigma\ \sigma^2 e^{-2\sigma} } &=& 4\left[ -\frac{1}{2}e^{-2D}D^2 -\frac{1}{2} e^{-2D}D - \frac{1}{4} e^{-2D} + \frac{1}{4} \right] \\\\ &=& -2e^{-2D}D^2 -2e^{-2D}D - e^{-2D} +1 \\\\ &=& -e^{-2D}(2D^2 +2D +1) +1 \\\\ &\mathbf{=}& \mathbf{1-e^{-2D}(2D^2 +2D +1) } \\ \hline \end{array}$$

heureka  Apr 10, 2018
#2
+418
0

i agree with heureka

jakesplace  Apr 10, 2018

### 30 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details